2019
DOI: 10.1039/c9cp00980a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the electronic structure properties of MoS2 monolayers with carbon doping

Abstract: The structural and electronic properties of MoS2 sheets doped with carbon line domains are theoretically investigated through density functional theory calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…In order to ensure a good compromise between the accuracy of our results and the computational feasibility, the tolerance in the density of the matrix and the total energy was set at 0.0001 and 0.00001 eV, respectively. Importantly, this set of parameters were used recently to study other carbon-based lattices 29 , 50 52 .…”
Section: Methodsmentioning
confidence: 99%
“…In order to ensure a good compromise between the accuracy of our results and the computational feasibility, the tolerance in the density of the matrix and the total energy was set at 0.0001 and 0.00001 eV, respectively. Importantly, this set of parameters were used recently to study other carbon-based lattices 29 , 50 52 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to studying the electronic structures of the bulk MoS 2 and the 2D MoS 2 , the fundamental experiments and theoretical studies have suggested that other variables may affect the material’s electrical properties, such as preparation methods [ 44 , 150 , 151 , 152 ], functionalization or doping [ 122 , 153 , 154 , 155 , 156 ], and environmental conditions [ 157 ]. For instance, many CVD-based methods for the synthesis of 2D MoS 2 have been developed, and changing experimental conditions, such as varying degrees of MoO 3 sulfurization during formation, can affect the material’s optical and electrical properties [ 150 ].…”
Section: Propertiesmentioning
confidence: 99%
“…According to the extensive dichalcogenide band structure calculations, the relevant Γ − 4 state at the top of the valence band is not a non-bonding metal state but rather an antibonding state between metal and non-metal orbitals [ 162 ]. There are several factors that can directly influence MoS 2 ’s optical properties, such as the electronic band structures, as described previously, quantum confinement effects, and functionalization or doping [ 6 , 149 , 155 , 162 ]. The quantum confinement triggers a distinct change in electronic or optical properties in nanomaterials [ 163 ].…”
Section: Propertiesmentioning
confidence: 99%
“…[18][19][20] Among the various TMDs, molybdenum sulphide (MoS 2 ) has received colossal attention due to its exceptional crystal structure, optical and electronic properties. [21,22] In a typical MoS 2 crystal structure, a hexagonal array of atomic Mo layers is sandwiched between the S layers with the existence of a strong covalent force between Mo and S and weak van der Waals interactions between the S layers. [23] In addition to their distinct structure, they also exhibit high electrocatalytic activity, specific surface area, thermal stability and structural flexibility making them suitable for fabricating various electronic devices such as batteries, supercapacitors, and biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal chalcogenides (TMDs) are layered materials that show a structure similar to that of GR, and hence find numerous applications in the field of optoelectronics and nano ‐ electronics. [18 – 20] Among the various TMDs, molybdenum sulphide (MoS 2 ) has received colossal attention due to its exceptional crystal structure, optical and electronic properties [21,22] . In a typical MoS 2 crystal structure, a hexagonal array of atomic Mo layers is sandwiched between the S layers with the existence of a strong covalent force between Mo and S and weak van der Waals interactions between the S layers [23] .…”
Section: Introductionmentioning
confidence: 99%